2022
DOI: 10.3390/polym14163257
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of the Anisotropy of the Stress-Optical Properties of Polyethylene Terephthalate Films Based on the Photoelastic Method

Abstract: Polyethylene terephthalate (PET) is one of the most commonly used substrate materials in the field of flexible electronics, and its stress-induced birefringence often has a detrimental effect on the optical properties of the device. Therefore, a deep and systematic understanding of the stress-optical properties of PET films is crucial for device design and manufacture. The photoelastic method is a direct optical measurement technique based on the stress-induced birefringence effect of materials, which has the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…To establish the relation between the wrapped original phase δ' 532 and δ' 1064 of the unloaded PET film, transmission photoelastic experiments at both 532 nm and 1064 nm wavelengths need to be conducted separately. In addition, the calibration experiments of stress-optical coefficients at both wavelengths can provide the relation between the stress-induced phase Δδ 532 and Δδ 1064 [12].…”
Section: Q He Et Al / a Transmission-reflection Photoelastic Combined...mentioning
confidence: 99%
“…To establish the relation between the wrapped original phase δ' 532 and δ' 1064 of the unloaded PET film, transmission photoelastic experiments at both 532 nm and 1064 nm wavelengths need to be conducted separately. In addition, the calibration experiments of stress-optical coefficients at both wavelengths can provide the relation between the stress-induced phase Δδ 532 and Δδ 1064 [12].…”
Section: Q He Et Al / a Transmission-reflection Photoelastic Combined...mentioning
confidence: 99%
“…For PET films, it was found that if uniaxial stretched, the refractive index corresponding to the tensile direction changes significantly as compared to the refractive index corresponding to the direction perpendicular to the tensile stress, while the birefringence exhibits a linear increase with strain [ 29 , 30 ]. This happens because large orientation effects were obtained in the stretching direction [ 31 ] due to PET’s ability to crystallize at large draw ratios during the deformation process [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The polymeric chains mostly lie in-plane during the fabricating process [ 34 ] and a supplementary applied uniaxial tension has a slight impact on the structure of the molecular chains situated in the out-of-plane direction [ 29 ]. In this way, the out-of-plane optical parameters are supposed to remain unchanged and only the in-plane optical properties modifications along the stretching direction are considered [ 29 , 30 ]. According to this, and due to the very close values of the two extraordinary refractive indices [ 35 ], it can be considered that, from an optical point of view, PET films act as uniaxial materials, and there is a single direction governing the optical anisotropy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indoor in the dark room, the melting temperature of aged bottles decreased from 249.8 The physical aging of semi-crystalline PET was studied using differential scanning calorimetry (DSC) at temperatures below the glass transition temperature (25 • C and 45 • C) in reference [14]. The results showed that after 120 days at 25 In reference [15], the anisotropy of the stress-optical properties of PET films under uniaxial stress was investigated. In paper [16], the tensile properties of three-layer A-PET films with different middle layer compositions were studied.…”
Section: Introductionmentioning
confidence: 99%